Definition of Development Activity as a Separate Type of Economic Activity - BLIAKHARSKYI, Yaroslav (University Scientific Notes, 2020)
The article is devoted to the research of development activities in the field of construction of buildings as a separate type of economic activity. An attempt is made to scientifically compare and contrast the concepts of «development activity» and «economic activity». The absence of legal regulation of development activities is noted, which leads to the uncertainty of legal relations in this area. In particular, this concerns the developer’s choice of the main and additional types of economic activities in accordance with the National Classifier of Ukraine «Classification of Economic Activities DK 009:2010» (hereinafter — «NACE»). The analysis of practice of developer’s choice of the main types of economic activities in accordance with the NACE is conducted in the article. The necessity of defining development activities as a type of economic activity in the NACE is substantiated, since such activities, in terms of their content, today cannot be fully attributed to any of the classes existing in the NACE. To confirm this position, the author reveals the scientific and legislative definition of «construction organization», compares the common and distinctive features of the categories «development» and «organization of building construction». Emphasis is placed on the inconsistency of the concepts used in class NACE 41.10 «Organization of building construction». The article provides arguments that the class of NACE 41.10 «Organization of building construction», although it is determined by the main type of economic activity for developers in practice, but it does not fully cover the content of development activities. Based on the results of the research, it is proposed to amend the class of NACE 41.10 «Organization of building construction» and supplement it with a new paragraph as follows: «organization in the interests of the customer of a set of actions for the development, direct implementation and attraction to financing of projects related to the creation or qualitative transformation of buildings, increasing their market value and investment attractiveness through the comprehensive preparation of a land plot for further development, construction of new or reconstruction of existing buildings (development activities)».